MODEL SUPERVISI WELL-BEING GURU BERBASIS MINDFULNESS DI ERA DIGITAL: KAJIAN LITERATUR - Ananda, Sri; Yusrianti, Susi (Jurnal Manajemen Pendidikan, 2025)
The development of the digital era has brought complex challenges for teachers, including increased workloads, emotional exhaustion, and demands for technological adaptation that impact their well-being. This study aims to analyze the potential of a mindfulness-based supervision model integrated with digital platforms to enhance teachers' well-being. Through a systematic literature review (2014–2024), it was found that mindfulness approaches such as meditation, self-reflection, and emotional regulation can reduce stress and improve teachers' mental resilience. The integration of technology through mobile applications, interactive webinars, and predictive analytics expands the accessibility and personalization of supervision programs. However, its implementation faces challenges such as the digital divide and resistance to change. The results of the study indicate that a hybrid (synchronous-asynchronous) model with empathetic supervisor guidance is an effective solution for creating a sustainable and humane supervision environment. This research recommends the development of an adaptive supervision framework that combines mindfulness principles with digital innovation, as well as the need for technology literacy training for teachers and supervisors. These findings contribute both theoretically and practically to the development of educational policies in the digital age.